Variation in Raw Milk Microbiota Throughout 12 Months and the Impact of Weather Conditions - Nan Li (Nature Portfolio, 2018)
Abstract Milk microbiota has a great influence on the safety and quality of dairy products. However, few studies have investigated the variations of bacterial composition in raw milk. In this study, raw milk samples were collected in 12 successive months, and their bacterial compositions were determined by 16 S rRNA gene sequencing. The highest diversity of bacterial composition was detected in June, while the lowest was in December. Firmicutes, Proteobacteria and Actinobacteria were the most abundant phyla and exhibited a counter-balanced relationship. Pseudomonas, Lactococcus and Acinetobacter were the most prevalent genera (>1%), and a tiny core microbiota (Acinetobacter and Pseudomonas) was observed. Temperature and humidity were the determining factors for most variation in bacterial compositions at both the phylum and genus levels. Higher abundances of Pseudomonas, Propionibacterium and Flavobacterium were correlated with low temperature. Furthermore, Pseudomonas/Propionibacterium and Lactobacillus/Bifidobacterium were two pairs of genera that had synergistic effects. Associations between the microbiota and milk quality parameters were analyzed. The abundances of Propionibacterium and Pseudoalteromonas were negatively correlated to total bacterial count, which meant that they helped to maintain milk quality, while a series of environmental microorganisms contributed to the spoilage of raw milk.